Rancang Bangun Aplikasi Manajemen Sales Force Berbasis Web Dan Android Dilengkapi Layanan Informasi Geografis (Studi Kasus Pada PT. Satryakarya Adiyudha) - Prawira Yudha, Anak Agung Ngurah; Sudarma, Made; Arsa Suyadnya, I Made (Jurnal SPEKTRUM, 2018)
This study aims to build a sales force system that can automate the marketing process in a company. Automation is necessary because manual calculations impact, in general on the company's sales performance, and in particular on sales performance. The solution offered on this issue is the development of a web-based sales force management application using PHP and HTML programming languages. While the Android-based applications built using Java and XML programming language. As a case study of workflow of sales force automation implementation, this study uses PT. Satryakarya Adiyudha which is a paint supplier and still working manually. The results obtained, an Android application to assist sales in conducting transactions, attendance, manage customer data, and calculate bonuses. While web applications are used by operators and managers in managing employee data, managing goods data, viewing sales visits, and confirming orders and printing order invoices. Based on Black-box testing, the result is functional applications can run well, whereas the Testing result using System Usability Scale (SUS) is 77.25 with Grade Scale C and Acceptability Ranges Acceptable.